The Effect of the TEMAN SETIA Program Intervention on Immunosuppressant Medication Adherence in Post-Kidney Transplant Patients at RSCM Jakarta - Suhartini, Euis; Nursanti, Irna; Natashia, Dhea; Irawati, Diana; Jumaiyah, Wati; Uly, Nilawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: Chronic Kidney Disease (CKD) poses a significant global health challenge, with an increasing number of kidney transplantations in Indonesia. The success of kidney transplants hinges on adherence to immunosuppressant medications to prevent organ rejection. Non-adherence among post-transplant patients can lead to infections, graft loss, or a return to dialysis. This study evaluated the impact of the TEMAN SETIA program on adherence to immunosuppressant medications among post-kidney transplant patients at Dr. Cipto Mangunkusumo National Referral Hospital (RSCM) in Jakarta. Methods: A pre-post-test design with a control group was utilized. The sample included 28 post-transplant patients meeting inclusion criteria. The TEMAN SETIA program provided patient mentoring to improve adherence. Adherence was assessed before the intervention, one month after, and two weeks post-intervention using a validated questionnaire. Data were analysed using t-tests and repeated measures ANOVA. Results: The control and intervention groups were comparable in demographic and clinical characteristics, though the intervention group had more non-working participants. The program significantly improved adherence (Cohen’s d = 1.97) and knowledge (Cohen’s d = 1.99). While family support increased in both groups, differences were not significant (Cohen’s d = 1.02). A significant group-by-time interaction (F (1.246, 26) = 7.394, p = 0.007, η² = 0.221) demonstrated greater adherence improvements over time in the intervention group. Discussion: The findings demonstrate that the TEMAN SETIA program is an effective intervention for enhancing medication adherence and knowledge among post-transplant patients. The structured mentoring approach provided patients with the necessary support and education to improve their adherence behaviors. Although family support increased in both groups, the changes were not statistically significant, highlighting the need for further exploration of the role of familial involvement in adherence programs Conclusion: The TEMAN SETIA program effectively enhanced medication adherence and knowledge in post-transplant patients. This structured intervention offers a promising strategy to improve outcomes and reduce risks of organ rejection.